Improving the Reading Ability of Elementary School Students in Recognizing the Nutritional Content of Carrots Through the Use of Mind Map - Alieta Nadia Marlitiana; Asri Wibawa Sakti (Media Pendidikan Gizi dan Kuliner, 2021)
Reading ability is a skill to gain knowledge and insight that will increase intelligence. At the elementary school level, it is still quite difficult to foster interest in reading, so that learning media is needed that can support teaching and learning activities. Thus, the purpose of this study was to determine the level of reading ability and understanding of elementary school students about the introduction of nutrients in carrots and the effect of using mind mapping on the learning process. The research method used is quantitative with data collection techniques through pre-test and post-test activities. The sample in this study amounted to 10 fifth-grade elementary school students. Based on the results of the pre-test and post-test activities on the introduction of the nutritional content of carrots using mind mapping, it showed a significant increase in students' reading and understanding abilities with an average increase of 74%. This shows that mind mapping can make the learning process fun and make students pay more attention. Based on the results of this study, it can be concluded that the use of mind mapping can help elementary students in improving their reading skills and understanding the relevant nutritional content of carrots.